Determinants of Preparedness Management and Nurses’ Response to COVID-19 Prevention Measures at a Government-Owned General Hospital in Indonesia (International Journal of Nursing Education, 2022)
Backgrounds: The increasing number of COVID-19 cases demands the preparedness of nurses as the front line inproviding health services to prevent being infected with COVID-19. This non-natural disaster has been declareda pandemic epidemic in the world so that efforts must be made to overcome itObjectives: The purpose of this study was to determine the factors that influence the management of preparednessand nurse response to COVID-19 prevention measures in a government-owned public hospital in a province inIndonesia.Methods: This quantitative study used a correlative design with a cross sectional approach to 220 nurses whowere selected using a proportionate stratified random sampling technique. The data were obtained using a selfreportquestionnaire and analyzed using the Chi-Square test and Logistic Regression.Results: The results showed that the effective response factor and facility readiness were the factors that mostinfluenced the nurse’s preparedness and response to COVID-19 prevention measures in hospitals. Nursesare expected can maintain their already very good preparedness so that no more nurses are infected with theCOVID-19 virus and are ready to be on standby with a new variant of the virus. Hospitals are expected tocarry out routine maintenance of facilities so that preventive measures for COVID-19 nurses can be carried outeffectively and appropriately and with adequate facilities and infrastructure.
Keywords: Preparedness, COVID-19, Prevention, Nurse, Hospital